2005
DOI: 10.1007/s11743-005-340-8
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion formation and detergency with oily soils: III. Performance and mechanisms

Abstract: The objective of this study was to investigate the correlation between oily soil removal efficiency and low oil-water interfacial tension (IFT) generated by microemulsion formation. A mixture of sodium dioctyl sulfosuccinate, alkyl diphenyl oxide disulfonate, and sorbitan monooleate was selected as a detergent formulation to evaluate detergency performance for two highly hydrophobic oils: hexadecane and motor oil. The maximum detergency corresponds to formation of a Winsor Type III microemulsion as well as to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
66
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 17 publications
(28 reference statements)
13
66
0
Order By: Relevance
“…One aspect not covered in this work is the use of additional rinsing steps to improve the oil removal. Based on recent studies on the effect of rinsing on microemulsionbased detergency, it is expected that the removal efficiency of all systems will improve with rinsing, especially for the cationic surfactant-rich system, due to changes in IFT and surfactant desorption (54).…”
Section: Resultsmentioning
confidence: 99%
“…One aspect not covered in this work is the use of additional rinsing steps to improve the oil removal. Based on recent studies on the effect of rinsing on microemulsionbased detergency, it is expected that the removal efficiency of all systems will improve with rinsing, especially for the cationic surfactant-rich system, due to changes in IFT and surfactant desorption (54).…”
Section: Resultsmentioning
confidence: 99%
“…However, if the system is operated in a Winsor Type III middle-phase microemulsion region, oil removal in the rinse step can be as high as that in the wash step. In addition, for highly hydrophobic oil such as motor oil, the oil was mostly removed in the rinse step instead of the wash step (12,20). In this present work, similar experiments were performed with the formulations S1 and S2.…”
Section: Figmentioning
confidence: 98%
“…These results suggest that the spreading effect that can be expected to occur when the system is operated at the second detergency maxima (D max2 ) as a result of the ultralow IFT. The mechanism of oily soil removal under the ultralow IFT condition resulting in spreading was explained in detail in a previous study (20).…”
Section: Figmentioning
confidence: 99%
“…Low or ultralow oil/water IFT and high solubilization can result from the presence of microemulsions in the system. The correlation between microemulsion formation and detergency has been noted in a number of studies [1,[7][8][9][10][11][12][13][14][15][16]. It has been shown that the maximum detergency corresponds to the optimum conditions of the system where the minimum oil/water IFT of the microemulsion exists [7,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies [13][14][15], formulation of mixed surfactants based on the linker concept were used to form microemulsions with both motor oil and hexadecane in detergency studies. The three surfactants used, in decreasing order of hydrophilicity, were: alkyldiphenyloxide disulfonate (ADPODS), sodium dioctyl sulfosuccinate (AOT), and sorbitan monooleate (Span 80).…”
Section: Introductionmentioning
confidence: 99%